The new career strategist: career management for the year 2000 and beyond. - Barner, Robert (Futurist)
An article adapted from Lifeboat Strategies: How to Keep Your Career Above Water During Tough Times—or Any Time. Profound economic and business changes in the U.S. and other industrialized countries are significantly altering the work world. Rather than using the linear approach of career planning, people will need to become career strategists, using a multidirectional, probabilistic model of career management. The focus will be on job resiliency, which involves developing the skills and flexibility to quickly respond to shifting employer requirements. The article presents steps for adapting to changing work situations and discusses the outlook for two-career couples, technical specialists, and educators. Models illustrating traditional career planning and the career strategist's approach are provided.